Small GTPases as regulators of cell division - Militello, Rodrigo Damián (2013)
The superfamily of small GTPases serves as a signal transducer to regulate a diverse array of cellular functions. The members of this superfamily are structurally and functionally classified into at least 5 groups (Ras, Rho/Rac, Rab, Arf, and Ran) and they are involved in the control of cell proliferation and differentiation, regulation of the actin cytoskeleton, membrane trafficking, and nuclear transport. It is widely reported that members of the Rab family participate in the control of intracellular membrane trafficking through the interaction with specific effector molecules. However, many Rabs and other small GTPases have also been shown to function in cell division. In this review, we discuss current knowledge about Rab proteins regulating different stages of the cell cycle, such as the congregation and segregation of chromosomes (during metaphase) and the final stage of cell division known as cytokinesis, in which a cell is cleaved originating 2 daughter cells.